Distribution features of sea surface temperature fronts in the Southeast region of Vietnam waters - Tu, Tran Anh; Cuong, Nguyen Kim; Uu, Dinh Van (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents an investigation of sea surface temperature front in the Southeast region of Vietnam using daily NOAA satellite images in April (dry season) and September (rainy season) for a period from 1985 to 2009. The method of Cayula and Cornilon (1992) for detecting the thermal front from satellite images was applied to evaluate the characteristics of the sea surface temperature front in the study area. The main features in front distribution, seasonal variations were described, and the relationship between front locations and fresh water discharge from Mekong river was qualitatively analyzed.